Collaboration Of Families, Schools, And Communities Through Tri Education Centers To Support Creativity And Innovation In Basic Education - Nurmayani; Mazaya Intan Putri; Claudia Zahra; Nurmaya Suci; Winda Julia Panena (Journal of Pedagogi, 2025)
Basic education is a crucial stage in forming the intellectual foundation, character, and skills of students. However, the orientation of education that still focuses on academic achievement makes the development of creativity and innovation less attention. This study aims to describe the collaboration between family, school, and community through the concept of Tri Center Education in supporting the creativity and innovation of elementary school students, as well as analyzing obstacles and mitigation strategies to maintain collaboration sustainability. The research method uses a qualitative approach with a case study design, involving school principals, teachers, parents, and community leaders as purposively selected informants. Data was obtained through in-depth interviews, participatory observations, and documentation studies, then analyzed with thematic techniques through coding, categorization, and triangulation of sources. The results show that family collaboration is seen in material, emotional, and ideative support; the community acts as an alternative space provider, mentor, and creative resource; while schools function as mediators that synergize both external actors. The impact of this collaboration appears in increased motivation, courage to experiment, and innovative works relevant to the socio-cultural context. Main obstacles include limited parental time, creative literacy capacity, communication gaps, limited facilities, and fluctuating commitments. Effective mitigation strategies include creative literacy training, flexible scheduling, liaison team formation, curriculum integration, external funding alliances, and participatory evaluations. In conclusion, the Tri Education Center can strengthen the creative and innovative education ecosystem if supported by systematic sustainability strategies.